EFEKTIVITAS METODE BREAST CARE PROLAKTIN ACCUPRESSURE DAN OXYTOCIN MASSAGE DALAM MENINGKATKAN PRODUKSI ASI PADA IBU POST PARTUM - Sudarianti; Rini Susanti (Program Studi S1/DIII-Keperawatan Universitas Imelda Medan, 2025)
Breast milk is the best nutrition for babies, especially during the first six months of life, playing an important role in boosting immunity, preventing stunting, and accelerating postpartum recovery in mothers. However, exclusive breastfeeding coverage remains low, with one of the causes being barriers to milk production during the early postpartum period. Non-pharmacological interventions such as breast care, prolactin acupressure, and oxytocin massage can stimulate hormones involved in breast milk production and ejection, but comprehensive studies comparing the three methods are still limited. This study aims to evaluate and compare the effectiveness of breast care, prolactin acupressure, and oxytocin massage in increasing breast milk volume in postpartum mothers. This study is a quasi-experimental study with a post-test control group design. The sample consisted of 60 postpartum mothers aged 0–7 days who met the inclusion criteria, then divided into four groups with 15 respondents each. The intervention was conducted over three days using standard procedures for breast care, prolactin acupressure, and oxytocin massage. Breast milk volume was measured on the fourth postpartum day using an electric pump for 15 minutes. Data analysis included normality tests, one-way ANOVA, and post hoc Tukey HSD. The results showed significant differences between groups (F = 86.342, p < 0.01). Oxytocin massage resulted in the highest breast milk volume and was significantly different compared to breast care (p < 0.001) and prolactin acupressure (p = 0.019), while breast care and prolactin acupressure were not significantly different (p = 0.561). These findings emphasize the importance of oxytocin stimulation in the let-down reflex and recommend oxytocin massage as the primary non-pharmacological intervention to support breast milk production.